Sequential mate choice in the South American fruit fly: the role of male nutrition, female size and host availability on female remating behaviour. Issue 4 (4th July 2018) - Abraham, Solana; Díaz, Viviana; Castillo, Gisela M.; Pérez-Staples, Diana
Abstract : After mating, female sexual receptivity usually decreases and returns, depending on various factors, one of which can be the quality of the first or second male. Here, we tested in the South American fruit fly Anastrepha fraterculus if female remating is conditioned by the quality of the second male, when females encounter sequential mates (under no-choice conditions) and when females have the opportunity to choose between well-nourished and malnourished males, both for mating and for remating. Additionally, we tested if other factors such as female size and the opportunity to oviposit influenced females' remating propensity. We found that females remate more often when they encounter a male of good nutritional condition, under both choice and no-choice conditions, and when females had access to a host to oviposit. Other traits of the sequential mate, such as male mating status (virgin or mated), male density (one or three males) and female size, had no effect on female remating behaviour. Plasticity in female post-copulatory mating under both choice and no-choice conditions indicates that A. fraterculus females are able to discriminate between males with different nutritional qualities without needing to compare them directly. Females were more choosy when remating, probably as a result of previous sexual experience, yet it remains to be seen which cues females use to distinguish between males. We discuss our results in the context of female pre- and post-copulatory mating decisions.